PENGARUH PENILAIAN KINERJA DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL MELALUI KEPUASAN KERJA PADA KANTOR BEA CUKAI PASURUAN - jurnalpps pps; Danang Seno Bintoro; Cathrine Sri Hartati; Ruddy Winarko (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
ABSTRACT Medium Customs and Excise Office Type A Pasuruan as a vertical institution within the Directorate General of Customs and Excise has problems related to organizational commitment which is suspected due to job discontent from employees related to performance appraisal and lack of employee motivation . This study aims to describe organizational commitment, job satisfaction, performance appraisal and employee motivation, to know and analyze the effect of performance appraisal and motivation on organizational commitment either directly or through job satisfaction, and to know whose influence is dominant over organizational commitment. This is an explanatory research with quantitative approach. Sampling using the technique of Proporsionate Stratified Random Sampling, consisting of echelon IV officials, echelon V officials and stafs with a total sample of 87 people. Hypothesis test using path analysis with trimming, and Sobel test to test the significance of indirect effect. The results of this study indicate that performance appraisal and motivation influence to job satisfaction, motivation and job satisfaction influence to organizational commitment, performance appraisal and motivation indirectly influence organizational commitment through job satisfaction, while performance appraisal does not directly influence to organizational commitment. Motivation influence dominant to organizational commitment. Keywords: organizational commitment, job satisfaction, performance appraisal, motivation